Effect of sintering temperature on the nature of weak links and flux pinning mechanism in La1.85Sr0.15CuO4 superconductor. Issue 1 (17th February 2015) - Sharma, Devina; Kumar, Ranjan; Awana, V P S
Abstract: AC and DC susceptibility study is carried out to investigate the granular nature of La1.85 Sr0.15 CuO4 superconductor. Presence of weak links and flux pinning phenomena are two important implications of granular type II high temperature superconductors. Weak links manifested as Superconductor-Insulator-Superconductor (SIS) / Superconductor-Normal metal-superconductor (SNS) Josephson Junctions are investigated from the temperature and field dependence study of AC susceptibility. On the other hand, DC susceptibility measurement is used to study the flux pinning mechanism. Mechanism of flux pinning is dependent on the nature and size of the pinning centres as well as on the microstructure wavelength. Thus, the nature of grain boundaries plays an important role in determining the nature of pinning mechanism of flux lines. In the present work, effect of sintering temperature on the nature of weak links and flux pinning mechanism in the bulk polycrystalline sample of La1.85 Sr0.15 CuO4 superconductor is studied.